ΔE1 and high-capacity adenoviral vectors expressing full-length codon-optimized merozoite surface protein 1 for vaccination against Plasmodium falciparum - Zong, Shan; Kron, Matthias W.; Epp, Christian; Engler, Tatjana; Bujard, Hermann; Kochanek, Stefan; Kreppel, Florian (The journal of gene medicine, 2011)
Background The merozoite surface protein (MSP)-1 of Plasmodium falciparum, the causative agent of malaria tropica, is considered to be a promising vaccine candidate. Although its stable cloning and expression has been difficult in the past, adenoviral vectors expressing the complex protein are described in the present study. Methods Codon-optimized msp-1 was used to construct a set of first generation (ΔE1Ad) and high-capacity adenovirus (HC-Ad) vectors, and cellular and humoral immune responses induced by the vectors were characterized in detail in mice. Results Generation of stable ΔE1Ad and HC-Ad vectors expressing full-length MSP-1 and their production to high vector titers was found to be feasible. Epitope identification and analysis of frequencies of specific CD8 T-cells revealed that MSP-1 expressing HC-Ad vectors induced higher frequencies of interferon-γ + CD8 T-cells than ΔE1 vectors. Irrespective of the vector format, higher titers of MSP-1 specific antibodies were generated by Ad vectors expressing MSP-1 from a chicken β-actin (CAG) promoter comprising the cytomegalovirus early enhancer element and the chicken β-actin promoter. Conclusions The findings of the present study suggest that Ad vectors expressing full-length codon-optimized MSP-1 are promising candidate vaccines against P. falciparum infections. Use of the HC-Ad vector type for delivery, as well as the CAG promoter to control MSP-1 expression, may further increase the efficacy of this vaccine candidate. Copyright © 2011 John Wiley & Sons, Ltd.